ANALYSIS OF THE DETERMINATION OF CIVIL CASE FEES IN THE DISTRICT COURT OF BANDA ACEH CITY : A STUDY OF SUPREME COURT DECISION No 03 of 2012 - Deva Sari, Putri; Rahmatillah, Syarifah; Jamhuri (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This study aims to evaluate the implementation of civil case fee provisions based on PERMA No. 03/2012 and identify factors that influence the high or low cost of case determination. The data collection method used was field research, which involved direct observation and interviews with relevant parties at the District Court of Banda Aceh City. In this study, it was found that the Banda Aceh City District Court has implemented the provisions of PERMA No. 03/2012 well. The management of case costs is conducted in a transparent and accountable manner, with clear details of costs provided to the parties. In addition, the mechanism for refunding costs for cases that were canceled or terminated was also applied in accordance with the provisions. The fee-setting process was conducted by taking into account various factors affecting the level of fees, including administrative and operational costs. The results of the study indicate that the costs of determining civil cases in the District Court of Banda Aceh City are in accordance with the provisions of PERMA, which supports the achievement of fair and transparent justice. This research confirms the importance of compliance with PERMA in ensuring that the fees charged are fair and in accordance with the applicable provisions, as well as providing the necessary protection for litigants.